O końcu i celu doświadczenia estetycznego - Shusterman, Richard (Er(r)go. Teoria - Literatura - Kultura, 2006)
Wojciech Małecki's Polish translation of "The End of Aesthetic Experience" in "Performing Live. Aesthetic Alternatives for the Ends of Art" by Richard Shusterman (2000).